Board Gender Diversity Codes, Quotas and Threats of Supranational Legislation: Impact on Director Characteristics and Corporate Outcomes - Martínez‐García, Irma; Terjesen, Siri; Gómez‐Ansón, Silvia (British journal of management, 2022)
We explore how a code, soft quota and a proposal for supranational law for board gender diversity affects women directors’ human capital characteristics and corporate outcomes with an unbalanced panel of 116 non‐financial firms and 1,321 firm‐year observations from 2003 to 2016 in Spain. Consistent with resource dependence theory, after a non‐punitive law is passed, boards seek to appoint more female directors who possess human capital attributes that will reduce uncertainty and bring necessary resources to firms. Compared with their pre‐law counterparts, the new female directors tend to have more human capital in terms of executive experience in non‐listed firms, and some non‐executive backgrounds, education and international experience; however, these new women directors generally possess less human capital than their male counterparts. Upper echelons theory suggests that board directors can meaningfully impact corporate outcomes. Overall, our results contradict upper echelons predictions about the impact of a regulation‐driven increase of women directors on corporate outcomes. Indeed, we find a lack of impact of the increase in women's presence on boards on corporate outcomes. Regarding policy, our findings substantially differ from those reported for countries with ‘hard law’ board gender quotas.